Resistance to Peloruside A and Laulimalide: Functional Significance of Acquired βI-tubulin Mutations at Sites Important for Drug-Tubulin Binding - Kanakkanthara, Arun; Eras, Jonathan; T. Northcote, Peter; Cabral, Fernando; H. Miller, John (Current Cancer Drug Targets, 2014)
Cancer cell lines selected for resistance to microtubule targeting agents (MTA) often have acquired mutations in the β-tubulin binding sites for these agents. Despite strong correlational evidence, the functional and quantitative significance of such mutations in the resistance to MTA remains unknown. We recently showed that peloruside A (PLA) and laulimalide (LAU)-resistant cancer cell lines, 1A9-R1 (R1) and 1A9-L4 (L4), generated through multi-step selection of human 1A9 ovarian cancer cells with high concentrations of either PLA (for R1) or LAU (for L4) have single distinct mutations in their βI-tubulin gene. The R1 cells have a mutation at amino acid position 296 (A296T), and the L4 cells have a mutation at position 306 (R306H/C), both of which lie at the putative binding sites of PLA and LAU. To gain insights on the functional role of these mutations in the resistance phenotype, R1 and L4 cells were transfected with wild type βI-tubulin. MTT cell proliferation assays revealed that restoration of wild type βI-tubulin expression partially sensitized the R1 and L4 cells to PLA and LAU. Cell cycle analysis and intracellular tubulin polymerization assays demonstrated that the increased sensitivity was correlated with an increased ability of PLA and LAU to induce G2-M arrest and tubulin polymerization in the cells. Unlike paclitaxel-selected clones of 1A9 cells, both R1 and L4 cells exhibited a functional p53 gene, and the abundance of the mismatch repair gene hMSH2 (human mutS homolog 2) was comparable to the parental 1A9 cells. This study provides the first direct evidence that A296 and R306 of βI-tubulin are important determinants of the PLA and LAU response in cancer cells.
Keywords: β-tubulin mutations